Drug diffusion transport through human skin - Walicka, Anna; Iwanowska-Chomiak, Beata (Zielona Góra: Uniwersytet Zielonogórski)
The stratum corneum (SC) forms the outermost layer of the human skin and is essentially a multilamellar lipid milieu punctuated by protein-filled corneocytes that augment membrane integrity and significantly increase membrane tortuosity. The lipophilic character of the SC, coupled with its intrinsic tortuosity, ensure that it almost always provides the principal barrier to the entry of drug molecules into the organism.
Keywords: drug delivery; human skin; diffusion